The Imperceptibility of Style in Danto's Theory of Art: Metaphor and the Artist's Knowledge. Issue 3 (December 2015) - Snyder, Stephen
Abstract : Arthur Danto's analytic theory of art relies on a form of artistic interpretation that requires access to the art theoretical concepts of the artworld, 'an atmosphere of artistic theory, a knowledge of the history of art: an artworld'. Art, in what Danto refers to as post-history, has become theoretical, yet it is here contended that his explanation of the artist's creative style lacks a theoretical dimension. This article examines Danto's account of style in light of the role the artistic metaphor plays in the interpretation of the artwork, arguing that it is unable to account for the metaphorical power he claims is embedded within the work of art. An artist's style issues from a unique perspective, the way an artist inhabits a specific spot in history. Though each person has such a perspective, when applied aesthetically, it is the key to the articulation of a unique historical meaning in the work of art. At the same time, artists' knowledge of their contribution remains cut off from this perspective, for they are unaware of their self-manifestation of the historical concept of style. This article makes the case that Danto's notion of style, based on Sartre's notion of being-for-itself, cannot fulfil the role he allots it in his theory because, at some level, artists must apprehend their style to create a work of art capable of functioning critically as a countertext. It is only through the apprehension of their style, and dialogical activity that takes place between the artist and the beholders, that the unseen body of artworld theory is formed. Without this, when oriented to the aesthetic, style provides no concept or theory for the mind to behold. This article presents an alternative approach to style that recognizes the role of theory in the creation of metaphor, which would circumvent this problem.